Preparation process of circuit board with high oxidation resistance
The reaction of green glue dandelion root polyphenols with formaldehyde to generate zinc oxide nanoparticles self-assembled microspheres and ceramic-based modifiers to improve the antioxidant performance and thermal stability of the circuit board, solve the oxidation and corrosion problems of the circuit board in the oxidation environment, and achieve efficient antioxidant performance and long life.
Patent Information
- Application Number
- CN202510470673.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-15
- Publication Date
- 2025-07-25
- Estimated Expiration
- 2045-04-15
AI Technical Summary
Existing circuit boards are prone to surface oxidation and metal layer corrosion problems in oxidation environments, resulting in reduced conductivity and shortened service life. The existing anti-oxidation treatment methods may lead to environmental pollution or local poor results.
The addition condensation reaction of green glue dandelion root polyphenols and formaldehyde to form formaldehyde resin, and zinc oxide nanoparticles are formed through zinc-ammonia complex, self-assembled into composite microspheres, combined with ceramic-based modifiers and epoxy resin to form a complex network structure, and prepared high-oxidation-resistant circuit boards.
It improves the antioxidant performance and thermal stability of the circuit board, prevents local oxidation, enhances the bonding force between the protective layer and the copper foil, and extends the service life of the circuit board.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of printed circuit boards, and particularly relates to a preparation process of a highly antioxidant circuit board. Background Art
[0002] With the rapid development of electronic technology, as a core component of electronic devices, the performance and quality of circuit boards directly affect the reliability and stability of electronic devices. Among various types of circuit boards, the demand for highly antioxidant circuit boards is becoming increasingly prominent. The usage environment of electronic devices is becoming increasingly complex, including harsh conditions such as high temperature, high humidity, and high corrosion, which puts higher requirements on the antioxidant performance of circuit boards.
[0003] At present, most circuit boards on the market are prone to problems such as surface oxidation and metal layer corrosion when facing an oxidation environment, thereby reducing the conductivity and service life of the circuit board. For example, in some high-temperature and high-humidity environments, metal parts such as copper foils on the circuit board will gradually be oxidized, resulting in an increase in circuit resistance and unstable signal transmission. Some existing antioxidant treatment methods, such as coating antioxidant agents and electroplating, although can improve the antioxidant performance of circuit boards to a certain extent, the electroplating process may produce pollutants such as waste water and waste gas, causing great pressure on the environment, while the method of coating antioxidant agents may have poor local antioxidant effects due to the unevenness of the coating.
[0004] Therefore, a preparation process of a highly antioxidant circuit board with uniform resistance is needed to extend the service life of the circuit board. Summary of the Invention
[0005] Aiming at the deficiencies of the existing technology, the purpose of the present invention is to provide a preparation process of a highly antioxidant circuit board.
[0006] A preparation process of a highly antioxidant circuit board includes the following steps: S1: Pretreat the copper foil Immerse the copper foil in absolute ethanol, ultrasonically clean it for 3 - 5 min, take it out, and then ultrasonically clean it with deionized water for 3 - 5 min to obtain the pretreated copper foil; S2: Surface antioxidant treatment Immerse the above pretreated copper foil in the antioxidant treatment agent, then place it in a rotary evaporator, set the water bath temperature at 25 - 35°C, rotate and evaporate for 20 - 30 min for surface coating, take it out, wash it with deionized water, and then bake it at 100 - 110°C for 10 - 20 min to obtain the antioxidant-treated copper foil; S3: Prepare the composite board Immerse the fiberglass cloth in the epoxy resin solution, and after drying, form a base material layer. Then attach the base material layer to one side of the above-mentioned antioxidant-treated copper foil to form a conductive layer. Next, coat the protective layer resin on the other side of the antioxidant-treated copper foil, and after drying and curing, form a protective layer to obtain a composite board with a "base material layer-conductive layer-protective layer" structure; S4: Prepare a highly antioxidant circuit board Perform post-treatment on the above composite board to obtain a highly antioxidant circuit board.
[0007] Further, the preparation steps of the antioxidant treatment agent are specifically as follows: Add alkyl benzimidazole and polyvinyl alcohol to deionized water, and stir well to dissolve to obtain solution A; Add gallic acid and triethanolamine to the above solution A, continue to stir, and dissolve thoroughly to obtain solution B; Add octylphenol polyoxyethylene ether to the above solution B, mix well, and then defoam to obtain the antioxidant treatment agent.
[0008] Further, the preparation steps of the protective layer resin are specifically as follows: Dissolve the ceramic-based modifier in N,N-dimethylformamide according to a solid-liquid ratio of 1 g:(20 - 30) mL, then add hein epoxy resin, stir and mix for 2 - 3 h, and then add zinc oxide composite microspheres, and stir and disperse thoroughly to obtain a mixed dispersion; Add tetramethyl bisphenol F cyanate to the above mixed dispersion, heat and stir at 100 - 120 °C for 3 - 4 h, and then perform vacuum defoaming to obtain the protective layer resin.
[0009] Further, the preparation steps of the ceramic-based modifier are specifically as follows: Add tetraethyl orthosilicate to absolute ethanol according to a volume ratio of 1:(25 - 35), stir at room temperature for 3 - 4 h, and dissolve thoroughly to obtain a tetraethyl orthosilicate solution; Add diphenylmethane diisocyanate and triethylamine to the above tetraethyl orthosilicate solution, stir for 4 - 6 h, then add zirconium propionate, continue to stir for 10 - 12 h, and then place it in a vacuum drying oven for vacuum drying to obtain the ceramic-based modifier.
[0010] Further, the preparation steps of the zinc oxide composite microspheres are specifically as follows: Add formaldehyde and polyethylene glycol to deionized water according to a solid-liquid ratio of (7 - 8) g:1 g:(500 - 600) mL, stir and mix evenly, and then add ammonia water to adjust the pH to 9 - 10 to obtain a mixed solution; Add cynanchum taraxacum root polyphenol and zinc sulfate heptahydrate to the above mixed solution according to a solid-liquid ratio of 1 g:(0.6 - 0.8) g:(200 - 300) mL, stir and mix evenly to obtain a mixed reaction solution; Transfer the above mixed reaction solution to a reaction kettle, heat it at 160 - 180 °C for 5 - 6 h to carry out continuous hydrothermal reaction. After natural cooling to room temperature, centrifuge, wash and dry it, and then cure it at 140 - 150 °C for 1 - 2 h to obtain zinc oxide composite microspheres.
[0011] Furthermore, the concentrations of each component in the antioxidant treatment agent include: 1 - 1.5 g / L alkyl benzimidazole, 5.5 - 6.5 g / L polyvinyl alcohol, 5.8 - 6.2 g / L gallic acid, 5 - 6 g / L triethanolamine, and 4.5 - 5.5 g / L octylphenol polyoxyethylene ether.
[0012] Furthermore, the mass ratio of hydantoin epoxy resin to the ceramic matrix modifier is (10 - 12):1.
[0013] Furthermore, the mass ratio of zinc oxide composite microspheres to hydantoin epoxy resin is 1:(8 - 10), and the mass ratio of tetramethyl bisphenol F cyanate ester to hydantoin epoxy resin is (3 - 4):1.
[0014] Furthermore, the volume ratio of diphenylmethane diisocyanate to tetraethyl orthosilicate solution is 1:(20 - 30), and the mass ratio of triethylamine to diphenylmethane diisocyanate is 1:(45 - 50).
[0015] Furthermore, the mass ratio of zirconium propionate to diphenylmethane diisocyanate is (3.4 - 3.6):1.
[0016] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. In the present invention, polyphenols from the roots of Taraxacum platypecidum Diels react with formaldehyde by addition and condensation under the catalysis of ammonia water to form formaldehyde resin. At the same time, zinc sulfate heptahydrate forms zinc oxide nanoparticles through "zinc - ammonia complex - zinc hydroxide - zinc oxide", and through the drive of surface tension and the interaction between zinc oxide and formaldehyde resin, "self - assembly" forms zinc oxide composite microspheres. Adding the zinc oxide composite microspheres to the protective layer resin, since zinc oxide can capture and neutralize the free radicals generated during the use of the protective layer resin, it can effectively improve the antioxidant performance of the protective layer resin, and thus improve the antioxidant performance of the circuit board. In addition, due to the coating effect of formaldehyde resin, it can improve the compatibility of nano - zinc oxide and epoxy resin, is conducive to the uniform dispersion of nano - zinc oxide, and prevents local oxidation problems from occurring during the use of the protective layer.
[0017] 2. The present invention first dissolves tetraethyl orthosilicate in absolute ethanol, then adds diphenylmethane diisocyanate, triethylamine and zirconium propionate, fully stirs and mixes them, and conducts vacuum drying to prepare a ceramic-based modifier with good dispersibility. After adding this ceramic-based modifier to the hydantoin epoxy resin, it can not only be evenly dispersed in the hydantoin epoxy resin, but also, due to the silicon and zirconium elements in the ceramic-based modifier being able to crosslink with the hydroxyl and epoxy groups in the hydantoin epoxy resin to form a more complex three-dimensional network structure, it can effectively improve the thermal stability of the hydantoin epoxy resin, and further contribute to improving the thermal stability of the protective layer.
[0018] 3. The present invention uses alkylbenzimidazole and polyvinyl alcohol as film-forming agents, gallic acid as an antioxidant, triethanolamine as a complexing agent, and combines with the surfactant octylphenol polyoxyethylene ether to prepare an antioxidant treatment agent. After immersing the pretreated copper foil in this antioxidant treatment agent, a stable complex film can grow on the surface of the copper foil, isolating the copper foil from the air, thereby preventing the copper foil from being oxidized by the air. In addition, the complex film grown on the surface of the copper foil can react with the functional groups in the protective layer resin, thereby enhancing the bonding force between the resin and the surface of the copper foil and preventing the protective layer from falling off. Specific embodiments
[0019] The following describes in detail the preparation process of a highly antioxidant circuit board provided by the present invention through specific examples. At the same time, it should be noted here that in order to make the examples more detailed, the following examples are the best and preferred examples, and those skilled in the art can also adopt other alternative methods for some well-known technologies.
[0020] Example 1 A preparation process of a highly antioxidant circuit board includes the following steps: (1) Preparation of the antioxidant treatment agent: Add alkylbenzimidazole and polyvinyl alcohol to deionized water, fully stir and dissolve to obtain solution A. Then add gallic acid and triethanolamine to solution A, continue stirring and fully dissolve to obtain solution B. Then add octylphenol polyoxyethylene ether to solution B, fully mix and homogenize, and then defoam to obtain the antioxidant treatment agent. Among them, the concentrations of each component in the antioxidant treatment agent are: 1 g / L alkylbenzimidazole, 5.5 g / L polyvinyl alcohol, 5.8 g / L gallic acid, 5 g / L triethanolamine, and 4.5 g / L octylphenol polyoxyethylene ether; (2) Preparation of the ceramic-based modifier: Add tetraethyl orthosilicate to absolute ethanol at a volume ratio of 1:25, stir at room temperature for 3 h, and dissolve it fully to obtain a tetraethyl orthosilicate solution. Then, add diphenylmethane diisocyanate and triethylamine to the tetraethyl orthosilicate solution, stir for 4 h, add zirconium propionate, continue to stir for 10 h, and then place it in a vacuum drying oven for vacuum drying to obtain a ceramic-based modifier. Among them, the volume ratio of diphenylmethane diisocyanate to the tetraethyl orthosilicate solution is 1:20, the mass ratio of triethylamine to diphenylmethane diisocyanate is 1:45, and the mass ratio of zirconium propionate to diphenylmethane diisocyanate is 3.4:1; (3)Prepare zinc oxide composite microspheres: Add formaldehyde and polyethylene glycol to deionized water at a solid-liquid ratio of 7 g:1 g:500 mL, stir and mix evenly, then add ammonia water to adjust the pH to 9 to obtain a mixed solution. Then, add Taraxacum mongolicum Hand.-Mazz. root polyphenols and zinc sulfate heptahydrate to the mixed solution at a solid-liquid ratio of 1 g:0.6 g:200 mL, stir and mix evenly to obtain a mixed reaction solution. Finally, transfer the mixed reaction solution to a reaction kettle, heat it at 160 °C for 5 h for continuous hydrothermal reaction, naturally cool it to room temperature, and then centrifuge, wash and dry it, and then cure it at 140 °C for 1 h to obtain zinc oxide composite microspheres; (4)Prepare a protective layer resin: Dissolve the ceramic-based modifier in N,N-dimethylformamide at a solid-liquid ratio of 1 g:20 mL, then add hein epoxy resin, stir and mix for 2 h, add zinc oxide composite microspheres, and stir and disperse fully to obtain a mixed dispersion. Among them, the mass ratio of hein epoxy resin to the ceramic-based modifier is 10:1, and the mass ratio of zinc oxide composite microspheres to hein epoxy resin is 1:8. Then, add tetramethyl bisphenol F cyanate ester to the mixed dispersion, heat and stir at 100 °C for 3 h, and then perform vacuum degassing to obtain a protective layer resin. Among them, the mass ratio of tetramethyl bisphenol F cyanate ester to hein epoxy resin is 3:1; S1: Pretreat the copper foil Immerse the copper foil in absolute ethanol, ultrasonically clean it for 3 min, take it out, and then ultrasonically clean it with deionized water for 3 min to obtain a pretreated copper foil; S2: Surface antioxidant treatment Immerse the above pretreated copper foil in an antioxidant treatment agent, then place it in a rotary evaporator, set the water bath temperature to 25 °C, and rotary evaporate for 20 min for surface coating. Take it out, wash it with deionized water, and then bake it at 100 °C for 10 min to obtain an antioxidant-treated copper foil; S3: Prepare a composite board The fiberglass cloth is impregnated in an epoxy resin solution, and after drying, a base material layer is formed. Then, the base material layer is attached to one side of the above-mentioned antioxidant-treated copper foil to form a conductive layer. Next, a protective layer resin is coated on the other side of the antioxidant-treated copper foil, and after drying and curing, a protective layer is formed, obtaining a composite board with a "base material layer-conductive layer-protective layer" structure; S4: Preparation of a highly antioxidant circuit board The above composite board is post-treated to obtain a highly antioxidant circuit board.
[0021] Example 2 A preparation process of a highly antioxidant circuit board includes the following steps: (1) Preparation of an antioxidant treatment agent: Alkyl benzimidazole and polyvinyl alcohol are added to deionized water and stirred thoroughly to dissolve, obtaining solution A. Then, gallic acid and triethanolamine are added to solution A, and stirring continues until fully dissolved, obtaining solution B. Next, octylphenol polyoxyethylene ether is added to solution B, and after thorough mixing and defoaming, an antioxidant treatment agent is obtained. Among them, the concentrations of each component in the antioxidant treatment agent are: 1.3 g / L alkyl benzimidazole, 6 g / L polyvinyl alcohol, 6 g / L gallic acid, 5.5 g / L triethanolamine, and 5 g / L octylphenol polyoxyethylene ether; (2) Preparation of a ceramic matrix modifier: Tetraethyl orthosilicate is added to absolute ethanol according to a volume ratio of 1:30, and stirred at room temperature for 3.5 h until fully dissolved, obtaining a tetraethyl orthosilicate solution. Then, diphenylmethane diisocyanate and triethylamine are added to the tetraethyl orthosilicate solution, stirred for 5 h, and then zirconium propionate is added, and stirring continues for 11 h. Then, it is placed in a vacuum drying oven for vacuum drying to obtain a ceramic matrix modifier. Among them, the volume ratio of diphenylmethane diisocyanate to the tetraethyl orthosilicate solution is 1:25, the mass ratio of triethylamine to diphenylmethane diisocyanate is 1:48, and the mass ratio of zirconium propionate to diphenylmethane diisocyanate is 3.5:1; (3) Preparation of zinc oxide composite microspheres: Formaldehyde and polyethylene glycol are added to deionized water according to a solid-liquid ratio of 7.5 g:1 g:550 mL, stirred and mixed evenly, and then ammonia water is added to adjust the pH to 9.5 to obtain a mixed solution. Then, cynanchum taraxacoides root polyphenol and zinc sulfate heptahydrate are added to the mixed solution according to a solid-liquid ratio of 1 g:0.7 g:250 mL, stirred and mixed evenly to obtain a mixed reaction solution. Finally, the mixed reaction solution is transferred to a reaction kettle, heated at 170 °C for 5.5 h for continuous hydrothermal reaction. After natural cooling to room temperature, it is centrifuged, washed, and dried, and then cured at 145 °C for 1.5 h to obtain zinc oxide composite microspheres; (4) Preparation of a protective layer resin: The ceramic-based modifier is dissolved in N,N-dimethylformamide at a solid-liquid ratio of 1g:25mL, and then hydantoin epoxy resin is added, and after stirring and mixing for 2.5 hours, zinc oxide composite microspheres are added, and fully stirred and dispersed to obtain a mixed dispersion, wherein the mass ratio of hydantoin epoxy resin to the ceramic-based modifier is 11:1, and the mass ratio of zinc oxide composite microspheres to hydantoin epoxy resin is 1:9, and then tetramethyl bisphenol F type cyanate is added to the mixed dispersion, heated and stirred at 110°C for 3.5 hours, and then vacuum degassing is performed to obtain a protective layer resin, wherein the mass ratio of tetramethyl bisphenol F type cyanate to hydantoin epoxy resin is 3.5:1; S1: Pre-treatment of copper foil The copper foil was immersed in anhydrous ethanol and ultrasonically cleaned for 4 minutes. After being taken out, it was ultrasonically cleaned with deionized water for 4 minutes to obtain a pretreated copper foil. S2: Surface antioxidant treatment The pretreated copper foil was immersed in the antioxidant treatment agent, and then placed in a rotary evaporator, the water bath temperature was set to 30°C, and the rotary evaporation was performed for 25 minutes to perform surface coating. After being taken out, it was washed with deionized water and then baked at 105°C for 15 minutes to obtain an antioxidant treated copper foil; S3: Preparation of composite sheet The glass fiber cloth is immersed in an epoxy resin solution and dried to form a substrate layer, and then the substrate layer is attached to one side of the anti-oxidation treated copper foil to form a conductive layer, and then a protective layer resin is coated on the other side of the anti-oxidation treated copper foil, and dried and cured to form a protective layer, thereby obtaining a composite plate with a "substrate layer-conductive layer-protective layer" structure; S4: Preparation of highly anti-oxidation circuit boards The composite board is post-processed to obtain a highly anti-oxidation circuit board.
[0022] Example 3 A preparation process of a highly anti-oxidation circuit board comprises the following steps: (1) Preparation of antioxidant treatment agent: Adding alkylbenzimidazole and polyvinyl alcohol into deionized water, stirring and dissolving them fully to obtain liquid A, then adding gallic acid and triethanolamine into liquid A, continuing stirring and dissolving them fully to obtain liquid B, then adding octylphenol polyoxyethylene ether into liquid B, mixing them fully and uniformly, and degassing to obtain an antioxidant treatment agent, wherein the concentrations of the components in the antioxidant treatment agent include: 1.5 g / L alkylbenzimidazole, 6.5 g / L polyvinyl alcohol, 6.2 g / L gallic acid, 6 g / L triethanolamine and 5.5 g / L octylphenol polyoxyethylene ether; (2) Preparation of ceramic-based modifiers: Add tetraethyl orthosilicate to absolute ethanol at a volume ratio of 1:35, stir at room temperature for 4 h, and dissolve thoroughly to obtain a tetraethyl orthosilicate solution. Then, add diphenylmethane diisocyanate and triethylamine to the tetraethyl orthosilicate solution, stir for 6 h, add zirconium propionate, continue to stir for 12 h, and then place it in a vacuum drying oven for vacuum drying to obtain a ceramic-based modifier. Among them, the volume ratio of diphenylmethane diisocyanate to the tetraethyl orthosilicate solution is 1:30, the mass ratio of triethylamine to diphenylmethane diisocyanate is 1:50, and the mass ratio of zirconium propionate to diphenylmethane diisocyanate is 3.6:1; (3)Prepare zinc oxide composite microspheres: Add formaldehyde and polyethylene glycol to deionized water at a solid-liquid ratio of 8 g:1 g:600 mL, stir and mix evenly, then add ammonia water to adjust the pH to 10 to obtain a mixed solution. Then, add Taraxacum mongolicum Hand.-Mazz. root polyphenols and zinc sulfate heptahydrate to the mixed solution at a solid-liquid ratio of 1 g:0.8 g:300 mL, stir and mix evenly to obtain a mixed reaction solution. Finally, transfer the mixed reaction solution to a reaction kettle, heat it at 180 °C for 6 h for continuous hydrothermal reaction, naturally cool to room temperature, and then centrifuge, wash and dry, and then cure at 150 °C for 2 h to obtain zinc oxide composite microspheres; (4)Prepare the protective layer resin: Dissolve the ceramic-based modifier in N,N-dimethylformamide at a solid-liquid ratio of 1 g:30 mL, add hein epoxy resin, stir and mix for 3 h, then add zinc oxide composite microspheres, and stir and disperse thoroughly to obtain a mixed dispersion. Among them, the mass ratio of hein epoxy resin to the ceramic-based modifier is 12:1, and the mass ratio of zinc oxide composite microspheres to hein epoxy resin is 1:10. Then, add tetramethyl bisphenol F cyanate ester to the mixed dispersion, heat and stir at 120 °C for 4 h, and then perform vacuum degassing to obtain the protective layer resin. Among them, the mass ratio of tetramethyl bisphenol F cyanate ester to hein epoxy resin is 4:1; S1: Pretreat the copper foil Immerse the above-mentioned pretreated copper foil in absolute ethanol, ultrasonically clean for 5 min, take it out, and then ultrasonically clean with deionized water for 5 min to obtain a pretreated copper foil; S2: Surface antioxidant treatment Immerse the copper foil in the antioxidant treatment agent, then place it in a rotary evaporator, set the water bath temperature to 35 °C, and rotate and evaporate for 30 min for surface coating. Take it out, wash it with deionized water, and then bake at 110 °C for 20 min to obtain an antioxidant-treated copper foil; S3: Prepare the composite board Immerse the fiberglass cloth in the epoxy resin solution, and after drying, form a substrate layer. Then attach the substrate layer to one side of the above-mentioned antioxidant-treated copper foil to form a conductive layer. Next, coat the protective layer resin on the other side of the antioxidant-treated copper foil, and after drying and curing, form a protective layer to obtain a composite board with a "substrate layer-conductive layer-protective layer" structure; S4: Prepare a highly antioxidant circuit board Perform post-treatment on the above composite board to obtain a highly antioxidant circuit board.
[0023] Comparative Example 1 The difference between this Comparative Example 1 and Example 1 is that step (3) is removed, and the zinc oxide composite microspheres in step (4) are removed.
[0024] Comparative Example 2 The difference between this Comparative Example 2 and Example 1 is that formaldehyde, polyethylene glycol, ammonia water, and Taraxacum mongolicum Hand.-Mazz. root polyphenols in step (3) are removed, that is, zinc sulfate heptahydrate is directly dissolved in deionized water for hydrothermal reaction to prepare nano-zinc oxide, and the zinc oxide composite microspheres in step (4) are replaced with an equal amount of nano-zinc oxide.
[0025] Comparative Example 3 The difference between this Comparative Example 3 and Example 1 is that step (2) is removed, and the ceramic-based modifier in step (4) is removed.
[0026] Comparative Example 4 The difference between this Comparative Example 4 and Example 1 is that step S2 is removed, that is, the surface of the pretreated copper foil is not subjected to antioxidant treatment.
[0027] Performance test: 1. Conduct an ultraviolet lamp weathering artificial aging test on the protective layers of the circuit boards prepared in Examples 1-3 and Comparative Examples 1-2 according to the standard of GB / T 23987-2009. The irradiation temperature is 60 °C and the irradiation time is 72 h, and evaluate the performance of the protective layer before and after aging according to the standard of GB / T 1776-2008. The results are shown in Table 1.
[0028] Table 1: Comparative table of antioxidant performance tests of the protective layers prepared in Examples 1-3 and Comparative Examples 1-2
[0029] As shown in Table 1, when zinc oxide composite microspheres were not added in Comparative Example 1, the light loss rate of the prepared circuit board protective layer was about 36.2% after the artificial aging test, which was much higher than that in Example 1. In Comparative Example 2, when zinc oxide composite microspheres were replaced with nano-zinc oxide, although the light loss rate of the prepared circuit board protective layer was not much higher than that in Example 1 after the artificial aging test, local excessive light loss occurred. Thus, it can be seen that through the addition condensation reaction of phenolic compounds from Taraxacum officinale roots with formaldehyde under the catalysis of ammonia water to form formaldehyde resin. At the same time, zinc sulfate heptahydrate forms zinc oxide nanoparticles through "zinc-ammine complex-zinc hydroxide-zinc oxide", and through the drive of surface tension and the interaction between zinc oxide and formaldehyde resin, "self-assembly" forms zinc oxide composite microspheres. When the zinc oxide composite microspheres are added to the protective layer resin, since zinc oxide can capture and neutralize the free radicals generated during the use of the protective layer resin, it can effectively improve the antioxidant performance of the protective layer resin, and further improve the antioxidant performance of the circuit board. In addition, due to the coating effect of formaldehyde resin, it can improve the compatibility between nano-zinc oxide and epoxy resin, which is beneficial to the uniform dispersion of nano-zinc oxide and prevent local oxidation problems during the use of the protective layer.
[0030] 2. The thermal stability of the circuit board protective layers prepared in Examples 1-3 and Comparative Example 3 was tested using a thermogravimetric analyzer. 5 mg of the protective layer was placed in a crucible, nitrogen was used as the protective gas, the temperature range was 30-500 °C, and the heating rate was 5 °C. The temperature at which the mass loss rate of each protective layer was 5% was measured. The results are shown in Table 2.
[0031] Table 2: Comparison table of the thermal stability test results of the protective layers in Examples 1-3 and Comparative Example 3
[0032] As shown in Table 2, when the ceramic-based modifier was not added in Comparative Example 3, the temperature at which the mass loss rate of the protective layer of the prepared circuit board was 5% under nitrogen was 395 °C, which was lower than that in Example 1. Thus, it can be seen that by first dissolving tetraethyl orthosilicate in absolute ethanol, then adding diphenylmethane diisocyanate, triethylamine, and zirconium n-propionate, fully stirring and mixing, and vacuum drying, a ceramic-based modifier with good dispersibility was prepared. After adding the ceramic-based modifier to the hydantoin epoxy resin, it can not only be evenly dispersed in the hydantoin epoxy resin, but also, due to the cross-linking reaction between the silicon and zirconium elements in the ceramic-based modifier and the hydroxyl and epoxy groups in the hydantoin epoxy resin, a more complex three-dimensional network structure is formed, which can effectively improve the thermal stability of the hydantoin epoxy resin, and further contribute to improving the thermal stability of the protective layer.
[0033] Test 3: The antioxidant-treated copper foils prepared in Examples 1-3 and the pretreated copper foil in Comparative Example 4 were respectively placed in an environment with a temperature of 40°C and a humidity of 70% for 72 h, and the surface was observed for corrosion spots. The results are shown in Table 3.
[0034] Test 4: Using a cross-cut adhesion tester, the adhesion of the protective layers prepared in Examples 1-3 and Comparative Example 4 was measured in accordance with GB / T 9286—1998. The results are shown in Table 3.
[0035] Table 3: Comparison table of test results of copper foil antioxidant performance and protective layer adhesion for Examples 1-3 and Comparative Example 4
[0036] As shown in Table 3, after the pretreated copper foil in Comparative Example 4 was placed in an environment with a temperature of 40°C and a humidity of 70% for 72 h, corrosion spots appeared on its surface, while no corrosion spots appeared on the surface of the antioxidant-treated copper foil prepared in Example 1. Thus, it can be seen that by using alkylbenzimidazole and polyvinyl alcohol as film-forming agents, gallic acid as an antioxidant, triethanolamine as a complexing agent, and cooperating with the surfactant octylphenol polyoxyethylene ether to prepare an antioxidant treatment agent, after immersing the pretreated copper foil in the antioxidant treatment agent, a stable complex film can grow on the surface of the copper foil, isolating the copper foil from the air, thereby preventing the copper foil from being oxidized by the air. In addition, the adhesion of the circuit board protective layer prepared in Comparative Example 4 to the copper foil was Grade 2, which was relatively poor compared to Example 1. It can be seen that the complex film grown on the surface of the copper foil can react with the functional groups in the protective layer resin, thereby enhancing the binding force between the resin and the copper foil surface and preventing the protective layer from falling off.
[0037] The above embodiments merely illustrate the principles and effects of the present invention and are not intended to limit the present invention. Any person familiar with this technology can modify or change the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or changes completed by those with ordinary knowledge in the technical field without departing from the spirit and technical ideas disclosed by the present invention should still be covered by the claims of the present invention.
Claims
1. A preparation process of a high-oxidation-resistance circuit board, characterized in that, It includes the following steps: S1: Pretreat the copper foil Immerse the copper foil in absolute ethanol and ultrasonically clean it for 3 - 5 min. After taking it out, ultrasonically clean it with deionized water for another 3 - 5 min to obtain the pretreated copper foil; S2: Surface antioxidant treatment Immerse the above pretreated copper foil in the antioxidant treatment agent, then place it in a rotary evaporator, set the water bath temperature at 25 - 35°C, and rotary evaporate for 20 - 30 min for surface coating. After taking it out, wash it with deionized water, and then bake it at 100 - 110°C for 10 - 20 min to obtain the antioxidant-treated copper foil; S3: Prepare the composite board Immerse the glass fiber cloth in the epoxy resin solution, dry it to form a base material layer. Then attach the base material layer to one side of the above antioxidant-treated copper foil to form a conductive layer. Next, coat the protective layer resin on the other side of the antioxidant-treated copper foil, dry and cure it to form a protective layer, and obtain a composite board with a "base material layer - conductive layer - protective layer" structure; S4: Prepare the highly antioxidant circuit board Perform post-treatment on the above composite board to obtain the highly antioxidant circuit board.
2. The preparation process of a highly antioxidant circuit board according to claim 1, characterized in that, The preparation steps of the antioxidant treatment agent are specifically as follows: Add alkyl benzimidazole and polyvinyl alcohol to deionized water, stir well to dissolve to obtain solution A; Add gallic acid and triethanolamine to the above solution A, continue to stir and dissolve completely to obtain solution B; Add octylphenol polyoxyethylene ether to the above solution B, mix well, and then defoam to obtain the antioxidant treatment agent.
3. The preparation process of a highly antioxidant circuit board according to claim 1, characterized in that, The preparation steps of the protective layer resin are specifically as follows: Dissolve the ceramic-based modifier in N,N-dimethylformamide according to the solid-liquid ratio of 1 g : (20 - 30) mL, then add the hein epoxy resin, stir and mix for 2 - 3 h, and then add zinc oxide composite microspheres, stir well to disperse to obtain a mixed dispersion; Add tetramethyl bisphenol F cyanate ester to the above mixed dispersion, heat and stir at 100 - 120°C for 3 - 4 h, and then perform vacuum defoaming to obtain the protective layer resin.
4. The preparation process of a highly antioxidant circuit board according to claim 3, characterized in that, The preparation steps of the ceramic-based modifier are specifically as follows: Add tetraethyl orthosilicate to absolute ethanol according to the volume ratio of 1 : (25 - 35), stir at room temperature for 3 - 4 h to dissolve completely to obtain a tetraethyl orthosilicate solution; Add diphenylmethane diisocyanate and triethylamine to the above tetraethyl orthosilicate solution, stir for 4 - 6 h, then add zirconium propionate, continue to stir for 10 - 12 h, and then place it in a vacuum drying oven for vacuum drying to obtain the ceramic-based modifier.
5. The preparation process of a highly antioxidant circuit board according to claim 3, characterized in that, The preparation steps of the zinc oxide composite microspheres are specifically as follows: Add formaldehyde and polyethylene glycol to deionized water according to the solid-liquid ratio of (7 - 8) g : 1 g : (500 - 600) mL, stir and mix evenly, and then add ammonia water to adjust the pH to 9 - 10 to obtain a mixed solution; Add cynanchum taraxacum root polyphenol and zinc sulfate heptahydrate to the above mixed solution according to the solid-liquid ratio of 1 g : (0.6 - 0.8) g : (200 - 300) mL, stir and mix evenly to obtain a mixed reaction solution; Transfer the above mixed reaction solution to a reaction kettle, heat it at 160 - 180 °C for 5 - 6 h to carry out continuous hydrothermal reaction. After naturally cooling to room temperature, centrifuge, wash and dry it, and then cure it at 140 - 150 °C for 1 - 2 h to obtain zinc oxide composite microspheres.
6. The preparation process of a highly antioxidant circuit board according to claim 2, characterized in that, The concentrations of the components in the antioxidant treatment agent include: 1 - 1.5 g / L alkylbenzimidazole, 5.5 - 6.5 g / L polyvinyl alcohol, 5.8 - 6.2 g / L gallic acid, 5 - 6 g / L triethanolamine, and 4.5 - 5.5 g / L octylphenol polyoxyethylene ether.
7. The preparation process of a highly antioxidant circuit board according to claim 3, characterized in that, The mass ratio of hydantoin epoxy resin to the ceramic matrix modifier is (10 - 12):
1.
8. The preparation process of a highly antioxidant circuit board according to claim 3, characterized in that, The mass ratio of zinc oxide composite microspheres to hydantoin epoxy resin is 1:(8 - 10), and the mass ratio of tetramethyl bisphenol F type cyanate ester to hydantoin epoxy resin is (3 - 4):
1.
9. The preparation process of a highly antioxidant circuit board according to claim 4, characterized in that, The volume ratio of diphenylmethane diisocyanate to tetraethyl orthosilicate solution is 1:(20 - 30), and the mass ratio of triethylamine to diphenylmethane diisocyanate is 1:(45 - 50).
10. The preparation process of a highly antioxidant circuit board according to claim 4, characterized in that, The mass ratio of zirconium propionate to diphenylmethane diisocyanate is (3.4 - 3.6):1.
Citation Information
Patent Citations
Conductor foil with adhesive layer, conductor-clad laminate, printed wiring board and multilayer wiring board
CN101432134A
Flame-retardant and high-temperature-resistant hydrocarbon resin glue solution and copper-clad substrate prepared from same
CN115772308A
Preparation method of rigid circuit board
CN116390381A
Epoxy resin composite material for copper-clad plate and preparation method of epoxy resin composite material
CN118702889A
Flexible material used for capacitors, preparation method therefor and printed circuit board
WO2020232691A1